Common grace as theological encouragement for interreligious dialogue - T. Salurante; D. Kristanto; M. Wibowo (Acta Theologica)
The Dutch theologian-statesman Abraham Kuyper developed the doctrine of common grace in a lengthy manner. Common grace emphasises that God’s grace operates not only in a salvific way for the elect, but also in a general way for every individual. Despite sin, human beings are capable of doing beautiful, just, and wise things and are endowed with gifts and talents, due to God’s act of common grace. On that doctrinal basis, Christians are called upon to appreciate the people outside the church, for there are fruits of common grace in their lives. On many occasions, Kuyper acknowledged that people of other religions have better qualities than Christians. Although not salvific, common grace opens various possibilities for Christians to learn from non-Christians. Thus, common grace could be a theological encouragement for interreligious dialogue toward mutual enrichment. This doctrine shows how the interreligious relationship between Christians and non-Christians should not be reduced to evangelism alone; it should also include dialogue and further cooperation toward the common good.